IDEOLOGICAL ANALYSIS OF ISLAMIC PHILANTHROPIC PRACTICES AND ITS IMPACT ON MUSTAHIK ECONOMIC EMPOWERMENT IN LAZISMU, EAST JAVA - Muhammad Alfi Syahrin (JSE: Jurnal Sharia Economica, 2025)
This study examines the ideological foundations of Islamic philanthropy practiced by Lazismu in East Java and its implications for mustahik economic empowerment. Rooted in Muhammadiyah’s principles of tajdid (renewal), amanah (trust), keadilan (justice), and maslahah (public welfare), Lazismu operationalizes zakat, infaq, and shadaqah funds through productive empowerment programs such as Bankziska, Tani Bangkit, and Kampung Berkemajuan. Using a qualitative case study approach, this research collected data through in-depth interviews, participant observation, and document analysis involving program managers, beneficiaries, and institutional stakeholders. The findings reveal that Muhammadiyah’s ideology functions as a strategic driver shaping program design, beneficiary selection, and governance mechanisms. Lazismu’s empowerment model demonstrates measurable socio-economic outcomes, including increased business turnover, enhanced agricultural productivity, and improved financial independence among mustahik. Moreover, the integration of vocational training, digital innovation, and moral education strengthens the sustainability and ethical orientation of empowerment initiatives. This study contributes to the moral economy discourse by illustrating how religious ideology, when institutionalized effectively, can transcend charitable redistribution and become a transformative framework for inclusive development. The results underscore that ideology-based Islamic philanthropy can serve as a viable model for faith-driven social enterprise and sustainable community empowerment.